2015
DOI: 10.1002/berj.3211
|View full text |Cite
|
Sign up to set email alerts
|

Childhood wellbeing: what role for education?

Abstract: The word wellbeing is ubiquitous in political discourse, and concerns about childhood wellbeing are particularly rife. This paper identifies, in the context of Scottish policy, how different professional discourses of wellbeing have migrated into education policy and it examines how this relates to learning. Taking a view of policy enactment as recontextualisation, the paper also explores how teachers and policy actors understand their role in supporting wellbeing. The paper shows how Scottish policy portrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 29 publications
(34 reference statements)
0
39
0
1
Order By: Relevance
“…What seems to have been more central for practitioners is the importance of listening to children. Spratt (2015) found that teachers' views tended to echo the written policy discourses on well-being, and recent years have seen considerable emphasis placed upon children's rights, and the importance of hearing children's voices. Globally, it is evident in the United Nations Convention on the Rights of the Child (1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What seems to have been more central for practitioners is the importance of listening to children. Spratt (2015) found that teachers' views tended to echo the written policy discourses on well-being, and recent years have seen considerable emphasis placed upon children's rights, and the importance of hearing children's voices. Globally, it is evident in the United Nations Convention on the Rights of the Child (1989).…”
Section: Discussionmentioning
confidence: 99%
“…Common to both reasons is the potential for the idea of wellbeing to be understood differently by different people, with consequent possible confusion and disagreement (Spratt, 2015). These differences in understanding then influence both what is measured, and how it is measured.…”
Section: Well-being: What Is It and Why Does It Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…It would be hard to argue that all ‘traditional’ approaches are antithetic to children's wellbeing, even if there are differences in emphasis and approach, while, as we have seen, there was a lack of consistency even under the ECM agenda (Ereaut & Whiting, ). Jennifer Spratt () offers a helpful typology of discourses in her exploration of wellbeing in Scottish educational policy. The development of children's policy in Scotland has diverged considerably from English models, particularly since 2010.…”
Section: Philosophy Policy and Classroom Practicementioning
confidence: 99%
“…Taking the Scottish Curriculum for excellence (Scottish Executive, ) and Getting it right for every child (Girfec) programmes (Scottish government, , 2012b), Spratt draws on Ereaut and Whiting () to suggest that there are potentially four themes (Spratt, : 225) which are implicit in discussions of wellbeing, although she emphasises that these are not mutually exclusive and several themes can be present within any particular approach. The four themes are: Theme 1: Discourse of physical health promotion, emerging from medicine Theme 2: Discourse of social and emotional literacy, emerging from psychology Theme 3: Discourse of care, emerging from the field of social care Theme 4: Discourse of flourishing, emerging from philosophy …”
Section: Philosophy Policy and Classroom Practicementioning
confidence: 99%